Estudio de factibilidad para determinar la rentabilidad económica y financiera sobre la implementación de un restaurant de comida de libre elección en la ciudad de Quevedo año 2012-2013 - Remache Lucio, Janina Elizeth (2013)
Food restaurant of choice will be established in the city of Quevedo, Los Rios province, for the purpose of providing specialized food service specializing in typical Ecuadorian food. The restaurant of choice will have wide acceptance since according to the proposal made, this type of service like people because they pay a fixed price and eat whatever they want, plus there fast service and variety on the menu. Importantly Ecuadorian food has a high market acceptance, love has both Ecuadorian and foreign. The reason for this project restaurant requires a total investment of $ 22,382.24 of which furnish the owner with $ 7.382.24 and the remaining $ 15,000 contribution will be financed with a loan from the local public banking term to four years, a 12% interest. The opportunity to install this type of restaurant is very important as it represents a business opportunity and it is an investment that has not been exploited in this city.